2(5c-1)-1=8c+9

Simple and best practice solution for 2(5c-1)-1=8c+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c-1)-1=8c+9 equation:


Simplifying
2(5c + -1) + -1 = 8c + 9

Reorder the terms:
2(-1 + 5c) + -1 = 8c + 9
(-1 * 2 + 5c * 2) + -1 = 8c + 9
(-2 + 10c) + -1 = 8c + 9

Reorder the terms:
-2 + -1 + 10c = 8c + 9

Combine like terms: -2 + -1 = -3
-3 + 10c = 8c + 9

Reorder the terms:
-3 + 10c = 9 + 8c

Solving
-3 + 10c = 9 + 8c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8c' to each side of the equation.
-3 + 10c + -8c = 9 + 8c + -8c

Combine like terms: 10c + -8c = 2c
-3 + 2c = 9 + 8c + -8c

Combine like terms: 8c + -8c = 0
-3 + 2c = 9 + 0
-3 + 2c = 9

Add '3' to each side of the equation.
-3 + 3 + 2c = 9 + 3

Combine like terms: -3 + 3 = 0
0 + 2c = 9 + 3
2c = 9 + 3

Combine like terms: 9 + 3 = 12
2c = 12

Divide each side by '2'.
c = 6

Simplifying
c = 6

See similar equations:

| 4/3=-3/2y-1/9 | | 4+m*3=1 | | 10p+10p+10=100+20+5p | | 4(3n-1)=(5n+4)+7 | | 1/3*e^(3-x) | | 1/7x-4/3=-1/2 | | 4v-2v=-4+14 | | 0=u^2+5u-24 | | 4x-62=x-1 | | 5m=3m-13 | | 11x+16=5x+40 | | 36+4y-7=16y-13-5y | | 5x(4x-1)=2 | | 9=2y-17y | | 7v-15v-16=-72 | | B^2+10b+26=0 | | 3(5c-1)-3=11c+6 | | 30ft^2-1n-3=0 | | 4a^2+16a+24=0 | | 7x-20=5X+32 | | w^2+2w-192=0 | | 25m^7n^2p^3/5m^5n^8p | | x^2+14x+y^2-12y=-4 | | -7=6v+34+3v | | x^2+14x+y^2-12y=-14 | | 3+4lnx=14 | | 7=x/22.4 | | X^4-20x^3+150x^2-500x+3125=0 | | 4(x+5)-1=27 | | 136721.93-.4x=36253.74 | | 3(x+1)-5x=2x+4(x-1) | | 19.2=v/6 |

Equations solver categories